Real‐Time Optical Process Monitoring for Structure and Property Control of Aerosol Jet Printed Functional Materials. Issue 12 (9th November 2020) - Tafoya, Rebecca R.; Cook, Adam W.; Kaehr, Bryan; Downing, Julia R.; Hersam, Mark C.; Secor, Ethan B.
Abstract: Aerosol jet printing is a popular digital additive manufacturing method for flexible and hybrid electronics, but it lacks sophisticated real‐time process control schemes that would enable more widespread adoption in manufacturing environments. Here, an optical measurement system is introduced to track the aerosol density upstream of the printhead. The measured optical extinction, combined with the aerosol flow rate, is directly related to deposition rate and accurately predicts functional materials properties such as the electrical resistance of printed graphene films. This real‐time system offers a compelling solution for process drift and batch‐to‐batch variability, rendering it a valuable tool for both real‐time control of aerosol jet printing and fundamental studies of the underlying process science. Abstract : An optical measurement system for aerosol jet printing is introduced to measure the aerosol density within the printhead, offering automated and rapid characterization of a physically‐relevant parameter highly predictive of printed functional material properties. This generalizable, real‐time monitoring is highly sought for digital printing technologies to support reliable production, fundamental insight, and advanced process control modalities.